Kinetics, Isotherm, Thermodynamics, and Recyclability of Exfoliated Graphene-Decorated MnFe2O4 Nanocomposite Towards Congo Red Dye - Van Thinh Pham; Hong-Tham T. Nguyen; Thuan Van Tran; Duyen Thi Cam Nguyen; Hanh T. N. Le; Thuong Thi Nguyen; Dai-Viet N. Vo; Thi Hong Nhan Le; Duy Chinh Nguyen (Journal of Chemistry)
Herein, we described the use of exfoliated graphene- (EG-) decorated magnetic MnFe2O4 nanocomposite (EG@MnFe2O4) for the removal and adsorption of Congo red (CR) dye from wastewater. Firstly, the precursors (EG, MnFe2O4) and EG@MnFe2O4 were fabricated, characterized using several physical analytical techniques such as X-ray powder diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), and N2adsorption/desorption isotherm measurement. For the adsorption experiments, the effect of contact time (0–240 min), concentration (10–60 mg/L), solution pH (2–10), adsorbent dosage (0.03–0.07 g), and temperature (283–313 K) was rigorously studied. To elucidate the adsorption mechanism and behaviour of CR over EG@MnFe2O4 and MnFe2O4 adsorbents, the kinetic models (pseudo-first-order, pseudo-second-order, Elovich, and Bangham) and isotherm models (Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich) have been adopted. The kinetic results indicated that models adhered to the pseudo-second-order equation, exhibiting the chemisorption mechanism in heterogeneous phrase. Meanwhile, the isotherm results revealed the adsorption of CR over EG@MnFe2O4 obeyed the monolayer behaviour (Langmuir model) rather than multilayer behaviour (Freundlich equation) over MnFe2O4. The thermodynamic study also suggested that such adsorption was an endothermic and spontaneous process. With high maximum adsorption capacity (71.79 mg/g) and good recyclability (at least 4 times), EG@MnFe2O4 can be a potential alternative for the adsorptive removal of CR dye from water.